2016
DOI: 10.1177/0954408915577338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inlet and outlet boundary conditions on the flow field of synthetic jets

Abstract: The present work provides the computations of unsteady 3D synthetic jet ejected into a quiescent ambient. The SST=k À ! turbulence model is employed for numerical simulations of flow field and the problem is considered under incompressible and axisymmetric assumptions. The pressure-implicit with splitting of operators algorithm is used for coupling of continuity and momentum equations. In order to accurately simulate the synthetic jet actuator, the dynamic mesh method is employed to model the flow field. In di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…They have concluded that momentum flux downstream of the jet exit is largely independent of the orifice inner lip radius and considerable power can be saved by rounding the inner lip. Bazdidi-Tehrani et al (23) have considered the flow fields ensuing from confined and unconfined synthetic jets. In order to understand the effects of the simulation of the actuator on the results, they have simulated it via the dynamic mesh method in two ways, namely, moving-piston and moving-diaphragm boundaries.…”
Section: March 2016mentioning
confidence: 99%
“…They have concluded that momentum flux downstream of the jet exit is largely independent of the orifice inner lip radius and considerable power can be saved by rounding the inner lip. Bazdidi-Tehrani et al (23) have considered the flow fields ensuing from confined and unconfined synthetic jets. In order to understand the effects of the simulation of the actuator on the results, they have simulated it via the dynamic mesh method in two ways, namely, moving-piston and moving-diaphragm boundaries.…”
Section: March 2016mentioning
confidence: 99%
“…Since this study allows the fluid to flow out of the computational domain naturally, the pressure outlet is chosen as the boundary condition, which helps to reduce the fluid reflection and flow disturbances at the end of the computational domain, thus improving the accuracy of the simulation. The basis for this choice is consistent with Xia et al [47] and Bazdidi et al [48]. A velocity inlet is positioned two L upstream, and a pressure outlet is situated four L downstream of the suboff model.…”
Section: Computational Domain and Boundary Conditionsmentioning
confidence: 74%
“…For the numerical simulation of synthetic jets, various turbulence modelling approaches such as Reynoldsaveraged Navier-Stokes (RANS) and large eddy simulation (LES) have been employed. [21][22][23][24][25] Although synthetic jets have received a lot of attention in the recent years, sufficiently detailed numerical investigations have not been conducted in this field due to the high computational costs. The capability of turbulence models to accurately simulate the flow field of a turbulent synthetic jet has first been studied by Tang and Zhong.…”
Section: Introductionmentioning
confidence: 99%